2015
DOI: 10.1021/acsbiomaterials.5b00045
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Synthesis and Quantitative Structure–Activity Relationship (QSAR) Modeling of Aminoglycoside-Derived Lipopolymers for Transgene Expression

Abstract: We describe the parallel synthesis of lipopolymers generated by conjugating alkanoyl chlorides to polymers derived from aminoglycoside antibiotic monomers as novel vehicles for transgene delivery and expression in mammalian cells. Parallel screening of lipopolymers led to the identification of six leads that demonstrated higher transgene expression efficacies in several cancer cells, when compared to the parental polymers as well as 25 kDa poly(ethylene imine), a current standard for polymer-mediated transgene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…In addition, folate‐targeted therapeutics have been investigated in clinical trials, which indicates the translational promise of this strategy . We have previously demonstrated that aminoglycoside‐derived polymers and lipopolymers demonstrated effective levels of transgene expression . Although aminoglycoside antibiotics can be nephrotoxic in their monomeric form, it is not clear if polymers derived from aminoglycosides demonstrate this activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, folate‐targeted therapeutics have been investigated in clinical trials, which indicates the translational promise of this strategy . We have previously demonstrated that aminoglycoside‐derived polymers and lipopolymers demonstrated effective levels of transgene expression . Although aminoglycoside antibiotics can be nephrotoxic in their monomeric form, it is not clear if polymers derived from aminoglycosides demonstrate this activity.…”
Section: Discussionmentioning
confidence: 99%
“…66 We have previously demonstrated that aminoglycoside-derived polymers and lipopolymers demonstrated effective levels of transgene expression. [36][37][38] Although aminoglycoside antibiotics can be nephrotoxic in their monomeric form, it is not clear if polymers derived from aminoglycosides demonstrate this activity. Given the high efficacy of these polymers, we hypothesized that conjugating ligands that can bind receptors on cancer cells can lead to targeted delivery vehicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QSPR approach is based on assumption that there is a mathematical relationship between a target activity (or property) of a chemical and its experimental or theoretical parameters (i. e. “descriptors”) . There is a limited number of research articles related to QSPR modeling of polymers . In these studies, researchers represent structures of polymers as minimal repeating units (monomers).…”
Section: Introductionmentioning
confidence: 99%
“…Over half a century later and thousands of papers disclosing applications in numerous areas including medicinal chemistry, [3][4][5] environmental, [6][7][8][9] food, [10][11][12] and material [13][14][15][16] sciences, as well as regulatory [17][18][19] across academy, industry, and government, QSAR has proved an invaluable tool for experts and non-experts alike in identifying patterns in datasets and assisting in the process of making quantitative predictions [20][21]. In drug discovery, QSAR represents a ligand-based method, which generates models by building relationships between structural information or properties for a set of compounds and related experimental data of interest (e.g., biological activity) as the target property [22][23].…”
Section: Introductionmentioning
confidence: 99%